PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING PADA PEMBELAJARAN IPA SMP POKOK BAHASAN PEMUAIAN ZAT - Mustika Wati Mustika Wati; Lisda Liana (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2011)
Abstract: The low of students’ motivation to learn physics, especially because of there is no variation in the model and the use of instructional media.Therefore conducted the study with the specific aim to describe: (1) increasing students’ motivation during the learning process of quantum teaching, (2) the teacher ability to manage learning by applying quantumteachingLesson Plan, (3) the studentactivities during the learning process of quantum teaching, (4) completeness of student learning after quantumteachinglearning model was applied.This study was comprised on 3 cycles of PTK.Data obtained from questionnaires, observation sheets, and tests.The findings of the studies are: (1) students motivation increasing isgood-qualified in all aspects of the cycle, attention amounted to 3.20; 3.05, and 3.38; the relevance of each aspect of 3.20; 3.09, and 3.26; confidence of 3.25; 3.57, and 3.44; satisfaction respectively by 3.24; 3.04, and 3.33, (2) the ability of teachers to manage learning based on the Lesson Planare 92%, 94% and 95% with an average reliability of 96% in both criteria (3) the student activity on very well categories with the percentage are 80.5%, 91%, and 92%, and (4) completeness of student learning in the classical are 63.16%, 76.19% and 85%.Based on these findings it can conclude that the effectiveness of quantumteaching learningmodels application to enhancing students' motivation in the expansionsubject is in effective category.Key words:Quantum teaching, expansion, motivation to learn, PTK